Soberania alimentar no Brasil: limites econômicos (geo)políticos e jurídicos nos marcos do capitalismo periférico - Guerra, Clarissa de Souza (2020)
Food Sovereignty is a multidimensional concept coined by social movements, notably Via Campesina, as a right of peoples to choose how they will organize the means of access, production and consumption of food. The main objective of this dissertation work is to try to answer what are the economic, (geo)political and legal limits that oppose the guarantee of such a right in the context of capitalism, mainly, of a peripheral capitalism, as is the case of Brazil. Aiming at building a response, the path of critical thinking was adopted, theoretically and methodologically, especially that of Marxist criticism of the capitalist mode of production. In view of the multidimensionality of the object under study, it was decided to emphasize issues related to the sustainability of productive systems, as well as those that involve the legal-political domain, with the following objectives: 1. Address primitive accumulation as the first expression of the metabolic failure in the relationship between human beings and the environment and contextualize Brazil, from colonization to agribusiness; 2. Analyze food sovereignty, as an evolving concept and a right that requires public policies, to understand the genesis of the concept and its environmental and legal dimensions; 3. Check the economic, geopolitical and legal limits to food sovereignty, based on the concrete reality of capitalist relations in their current phase. In conclusion, it can be said that the guarantee of food sovereignty, in its legal and environmental dimensions, is connected with the adoption of sustainable productive practices (agroecological), the democratization of access to natural resources, especially land (land reform) and the realization of the human right to adequate food. These aspects led the Brazilian State to develop, based on the formalization of the concept of food sovereignty, in 1996, public policies and to issue laws, aimed at fulfilling this right. However, before any obstacle, the guarantee of food sovereignty finds limits in the capitalist system itself: economic, due to the financialization of capital; geopolitical, due to neoliberalism and the configurations of global geopolitics; and legal, because the law, in its appearance (normative apparatus) does not, by itself, achieve food sovereignty, due to the limitations arising from its essence, that is, as a specific form of capitalism. In this context, the political use of legal norms presents itself as a possibility for a new sociability, since the guarantee of food sovereignty, in its fullness, does not find space within the scope of the capitalist system.